The Role of Economic Freedom in Interpreting Corruption Perception - Yangins, Gulcin; Deprens, Serpil Kilic (HIPATIA PRESS, 2021)
The main purpose of the study is to examine the nexus between corruption and economic freedom to determine the most influencing factors to be focused on to reduce corruption. With this aim, two different machine learning algorithms are performed to find out the single effect, two-way, and three-way interaction effects of factors affecting corruption. As a result of the analysis, tax burden, government integrity, and government spending are the main indicators to be focused on to improve corruption steadily. Besides, critical thresholds of the tax burden, government integrity, and government spending are 83.3, 50.9, and 40.6, respectively. Since there are a limited number of studies to predict corruption by machine learning algorithms in the extant literature, this research provides highly detailed information to policy-makers where they can focus on reducing corruption perception.
Keywords: economic freedom; multivariate adaptive regression splines; corruption perception; MODEL; Social Sciences - Other Topics